Universal 2 Wrist Arthroplasty in Rheumatoid Arthritis - Pfanner, Sandra; Munz, Giovanni; Guidi, Giulia; Ceruso, Massimo (Journal of Wrist Surgery, 2017)
Purpose The aim of this study was to evaluate the mid- to long-term outcomes and complications in patients affected by rheumatic diseases treated with the Universal 2 (U2) total wrist arthroplasty (TWA).Methods We reviewed, in a retrospective, noncontrolled cohort study, 22 patients affected by rheumatoid arthritis (RA), who underwent U2 total wrist replacement between March 2003 and January 2014 for the treatment of 23 rheumatoid wrists with the aim of obtaining the remission of pain and a range of motion (ROM) useful for daily activities, according to the patients' demands, as an alternative to total wrist arthrodesis. The cohort of patients included 20 females and 2 males, with a mean age of 54.9 years. Residual pain, preoperative ROM, postoperative ROM increases, grip strength, radiographic changes, long-term complications, and reasons for revision or failures were evaluated.Results In this study, 22 patients were evaluated at a mean follow-up of 82.3 months (range: 2–12 years). All patients had good or complete pain relief, the mean visual analogue scale pain score was 0.82. The mean grip strength improved and postoperatively was 11 kg (Jamar). The mean total ROM of flexion–extension was 72.3 degrees; radial–ulnar deviation 24.9 degrees. The mean QuickDASH score of 49 and patient rate wrist/hand evaluation of 41.7 a revision surgical procedure in six cases (26%): in two cases, a carpal component revision procedure and in four cases, total implant failures requiring either conversion to a Swanson spacer or wrist joint fusion.Conclusion TWA provides pain relief, preserves motion, and improves function in severe degenerative RA. Our results at a mid- to long-term follow-up with the U2 prosthesis were encouraging and represent, when indicated, a valid alternative to fusion which is less appealing for RA patients. Level of Evidence Level of evidence is therapeutic IV.
Keywords: wrist joint; total wrist arthroplasty; rheumatoid arthritis; Universal 2